ANALISIS KEPUASAN PELANGGAN TERHADAP PEMANFAATAN FACEBOOK COMMERCE MENGGUNAKAN METODE IMPORTANCE PERFORMANCE ANALYSIS (IPA) - Vivi Sahfitri (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2017)
The Model of Electronic commerce or better known as e-commerce increasingly in demand by the public at large. This electronic transaction model was born because of the globalization of information technology in the economic field. The ease of doing transactions without having to go directly to producers who sell an item makes the widespread of electronic trading activities. Social network is one of the electronic commerce media that currently has many users. This research has purpose to analyze customer satisfaction to utilize facebook Commerce using Method of Importance Performance Analysis (IPA). The result of this research is expected to provide empirical evidence about factors influencing customer satisfaction and facebook commerce user in conducting online transactions. In addition, the test results are also expected to provide insert for improvement for the manager or owner of e-commerce on facebook in order to be more trusted so as to increase online sales made.